Low vitamin D levels are associated with symptoms of depression in young adult males - Black, Lucinda; Jocoby, P.; Allen, K.; Trapp, G.; Hart, P.; Byrne, S.; Mori, T.; Beilin, L.; Oddy, W. (Sage Publications Ltd., 2013)
Objective: Results from studies examining associations between serum 25-hydroxyvitamin D (25(OH)D) concentrations and depressive symptoms are equivocal. We investigated the relationship between serum 25(OH)D concentrations and symptoms of depression, anxiety and stress in a cross-sectional analysis of a population-based sample of young adults participating in the Western Australian Pregnancy Cohort (Raine) Study. Methods: Participants provided a blood sample at the 20-year follow-up (March 2010-April 2012) for the measurement of serum 25(OH)D concentrations. Mental health symptoms were assessed using the 21-item Depression Anxiety Stress Scales (DASS-21). Associations between serum 25(OH)D concentrations and total DASS-21 scores and subscale scores of depression, anxiety and stress were explored in males and females using negative binomial regression, adjusting for age, race, body mass index (BMI) and physical activity (n=735). Models examining subscale scores were also adjusted for the other subscale scores. Results: After adjusting for confounders, an increase in serum 25(OH)D concentrations of 10 nmol/L decreased total DASS-21 scores in males by 9% (rate ratio (RR) 0.91; 95%CI 0.87,0.95; p<0.001) and depression subscale scores in males by 8% (RR 0.92; 95%CI 0.87,0.96; p=0.001). However, in adjusted models there were no significant associations between serum 25(OH)D concentrations and symptoms of anxiety and stress in males. There were no significant associations between serum 25(OH)D concentrations and symptoms of depression, anxiety and stress in females. Conclusions: We found an association between serum 25(OH)D concentrations and symptoms of depression, but not anxiety and stress, in males. Randomised controlled trials are necessary to determine any benefit of vitamin D supplementation in the prevention and treatment of depressive symptoms in young adults.